Understanding the expression of signalling pathway marker genes associated with bacterial wilt in susceptible and resistant ginger sps. (August 2021) - Mohandas, Snigdha; Venugopal, Vidya; Duraisamy, Prasath
Abstract: Ralstonia solanacearum causes bacterial wilt in ginger. Here the role of signalling pathways such as salicylic acid (SA), ethylene (ET) and jasmonic acid (JA) was studied by comparing the differential expression of the marker genes for these pathways during bacterial wilt in both susceptible (ginger, Zingiber officinale ) and resistant (mango ginger, Curcuma amada ) ginger species. When expression of marker genes was compared among susceptible and resistant ginger sps., SA pathway marker genes, non-expressor of PR1 genes (NPR1) and TGACG sequence-specific binding protein (TGA6) and the ET pathway marker genes, AP2 domain class transcription factor (AP2) and 4-Coumarate: CoA ligase (4CL1), were expressed with a statistically different (p < 0.05) fold change among susceptible and resistant ginger sps in all time intervals. Expression of marker genes in resistant ginger showed higher expression in the first-hour post inoculation itself; however, marker genes of susceptible ginger had a slow pace in expression. Even though the marker genes of JA such as allene oxide cyclase (AOC) and lipoxygenase (LOX2) were activated in the initial hour post-inoculation in both ginger sps, their expression of these marker genes were significantly at par (p < 0.05) among ginger species in almost all time intervals. These results indicate that even though JA is activated upon infection, SA and ET signalling pathways play an essential role in giving resistance to resistant ginger. Moreover, the time and magnitude of expression play a higher impact on host-pathogen resistance. Understanding the role of signalling pathways involved in bacterial wilt resistance in resistant ginger can provide insights into host-pathogen resistance in ginger, which can help develop wilt-resistant ginger. Highlights: An interplay of signalling pathways confers ginger species its difference in bacterial wilt resistance. Significant difference in expression of marker genes of SA and ET were observed among susceptible and resistant gingers. The expression of marker genes were higher in initial hours post inoculation for resistant than susceptible species. Significantly no difference was observed in the expression of makers genes of JA among two species. Magnitude and time of gene expression of signalling pathways confers the difference in bacterial wilt resistance in gingers.